Sliding materials and fluid machinery
A composite sliding member with a resin-based first material and fluorine resin particles, combined with a fluorine resin and reinforced agent, addresses wear resistance issues in fluid machines by forming a transfer film, enhancing durability and reducing friction.
Patent Information
- Application Number
- JP2021055927
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2041-03-29
AI Technical Summary
Existing sliding members in fluid machines, such as reciprocating gas compressors, suffer from inadequate wear resistance due to the limitations of materials like fluorine resin, leading to issues like excessive thermal expansion and peeling of transfer films.
A composite sliding member composed of a first material, including a resin other than fluorine resin with dispersed fluorine resin particles and rod-shaped particles, and a second material comprising fluorine resin and a reinforced agent, which together form a transfer film to enhance wear resistance.
The composite sliding member significantly reduces friction coefficient and wear resistance, improving the longevity and performance of components in high-temperature environments like reciprocating gas compressors.
Smart Images

Figure 0007623872000002 
Figure 0007623872000003 
Figure 0007623872000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sliding material and a fluid machine. [Background technology]
[0002] As a fluid machine capable of compressing or expanding a gas, for example, a reciprocating type fluid machine (gas compressor, etc.) is known. Reciprocating type fluid machines include normal piston type fluid machines and oscillating piston type fluid machines. The former type of fluid machine has a bearing at the compression / expansion chamber side end of the connecting rod, and a piston supported by the bearing so as to be able to oscillate. The latter type of fluid machine has a piston integrated with the connecting rod, without having a bearing at the compression / expansion chamber side of the connecting rod. Of these, in the oscillating piston type fluid machine, the gas is compressed by the piston reciprocating while oscillating within a metal cylinder. The piston has a sliding member that slides on the inner circumferential surface of the cylinder, and examples of the sliding member include a lip ring and a piston ring.
[0003] As a technology relating to sliding members, Patent Document 1 describes "a piston for a cylinder, characterized in that in a cylinder device comprising a cylinder and a piston that engages with the inner peripheral surface of the cylinder via a piston ring, the piston ring is formed on the outer peripheral part of the piston by insert molding using a resin composition containing as essential components 60 to 80 weight % polyphenylene sulfide (PPS) resin, 10 to 30 weight % fluororesin, 2 to 10 weight % spherical filler, and 2 to 10 weight % fibrous filler." [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 3-74681 Summary of the Invention [Problem to be solved by the invention]
[0005] Although details will be described later with reference to examples, the technique described in Patent Document 1 leaves room for improvement in terms of wear resistance of the sliding members. An object of the present disclosure is to provide a sliding member and a fluid machine having excellent wear resistance. [Means for solving the problem]
[0006] The sliding member of the present disclosure is a sliding member that comes into contact with a sliding surface, and the sliding member includes a first member that is made of a first material including a first base resin made of a resin other than a fluororesin, fluororesin particles and rod-shaped particles dispersed in the first base resin, and a first member that is made of a first material including a first base resin made of a resin other than a fluororesin, and a first material including a first base resin made of a resin other than a fluororesin, and a rod-shaped particle dispersed in the first base resin. The sliding direction of the sliding member in and a second member arranged adjacent to the first member along the line, the second member being made of a second material including a second base resin made of a fluororesin and a reinforcing agent dispersed in the second base resin. Other solutions will be described later in the description of the embodiment of the invention. Effect of the Invention
[0007] According to the present disclosure, it is possible to provide a sliding member and a fluid machine having excellent wear resistance. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a cross-sectional view showing a sliding member of the first embodiment. [Diagram 2] FIG. [Diagram 3] FIG. [Figure 4] 1A and 1B are diagrams illustrating a transfer film formed during sliding. [Diagram 5] 1 is a schematic diagram of a fluid machine including a sliding member of a first embodiment. [Figure 6] FIG. 11 is a cross-sectional view showing a sliding member of a second embodiment. [Figure 7] FIG. 2 is a diagram illustrating a test method for a friction test. [Figure 8] 1 shows an energy dispersive X-ray analysis image of the surface of a test piece after a friction test. [Figure 9]FIG. 1 is a diagram showing test results of wear volume and friction coefficient obtained in a friction test. [Figure 10] FIG. 4 is a graph showing the correlation between the wear amount and friction coefficient obtained in a friction test and the content of fluororesin particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, a form for carrying out the present disclosure (referred to as an embodiment) will be described with reference to the drawings. In the following description of one embodiment, other embodiments applicable to the one embodiment will also be described as appropriate. The present disclosure is not limited to the following one embodiment, and different embodiments can be combined with each other or modified as desired without significantly impairing the effects of the present disclosure. In addition, the same symbols will be used for the same members, and duplicate descriptions will be omitted. Furthermore, members having the same functions will be given the same names. The contents shown are merely schematic, and for convenience of illustration, changes may be made from the actual configuration within a range that does not significantly impair the effects of the present disclosure, and some members may be omitted or modified between drawings.
[0010] 1 is a cross-sectional view showing a sliding member 12 of the first embodiment. The sliding member 12 comes into contact with a sliding surface 13, which is, for example, an inner wall surface of a metal member 11. In the illustrated example, the sliding member 12 reciprocates (moves up and down) up and down as indicated by solid arrows while sliding on the sliding surface 13. The sliding member 12 is configured as, for example, a piston 40 (FIG. 5). The sliding member 12 includes a first member 12a and a second member 12b.
[0011] 2 is a cross-sectional view of the first member 12a. The first member 12a is made of a first material, and the first material includes a first base resin 21 made of a resin other than fluororesin, and fluororesin particles 22 and rod-shaped particles 23 dispersed in the first base resin 21. The particles are preferably dispersed evenly throughout the first base resin 21, but may be unevenly distributed in some areas.
[0012] The first base resin 21 forms the outer shell of the first member 12a. The first base resin 21 is not particularly limited as long as it is made of a resin other than fluororesin and can function as the sliding member 12, but among them, a resin with excellent heat resistance and low thermal expansion coefficient is preferable. Specific examples include polyphenylene sulfide (PPS), polyether ether ketone (PEEK), polyether sulfone (PES), phenolic resin (PF), polyimide (PI), and modified products thereof. The first base resin 21 may be used alone or in any ratio and combination of two or more kinds.
[0013] The first base resin 21 preferably contains at least one of polyphenylene sulfide and polyether ether ketone. By containing these polymers, the heat resistance of the first member 12a can be improved.
[0014] When sliding on a sliding surface 13 (FIG. 1), the fluororesin particles 22 transfer to the sliding surface 13 to form a transfer film 14 (FIG. 4) on the sliding surface 13. The constituent material of the fluororesin particles 22 is not particularly limited as long as it is a fluororesin, and examples thereof include polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkylvinylether copolymer (PFA), tetrafluoroethylene-ethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), etc. The constituent material of the fluororesin particles 22 may be one type alone, or two or more types may be used in any ratio and combination.
[0015] The fluororesin particles 22 preferably contain at least one of polytetrafluoroethylene and a tetrafluoroethylene-perfluoroalkylvinylether copolymer. By using these polymers, the formation of a transfer film 14 on the sliding surface 13 (FIG. 1) caused by the fluororesin particles 22 can be promoted.
[0016] The form of the fluororesin particles 22 is not particularly limited as long as it does not significantly impair the effects of the present disclosure, but may be, for example, particulate (granular). The particle size of these particles may be, for example, 5 μm or more and 200 μm or less. The particle size may be measured as an average particle size that can be measured using, for example, a laser diffraction particle size distribution measuring device.
[0017] The content of the fluororesin particles 22 is not particularly limited as long as it does not significantly impair the effects of the present disclosure, but is preferably 15% by mass or more and 30% by mass or less with respect to the first material. By setting the content in this range, excessive thermal expansion of the first member 12a caused by the fluororesin particles 22 can be suppressed, and the friction coefficient of the first member 12a with respect to the sliding surface 13 (FIG. 1) can be reduced. Furthermore, peeling of the transfer film 14 (FIG. 4) caused by the fluororesin particles 22 can be suppressed. As a result, the wear resistance of the sliding member 12 can be particularly improved.
[0018] The rod-shaped particles 23 improve the strength of the first member 12a against stress such as tensile stress due to their rod-shaped form. The rod-shaped particles 23 can be made of any material as long as it does not significantly impair the effects of the present disclosure, but preferably contain at least one of carbon fiber and glass fiber. By using these fibers, the rod-shaped particles 23 can be made using easily available fibers.
[0019] The length and diameter of the rod-shaped particles 23 are not particularly limited as long as they do not significantly impair the effects of the present disclosure, but for example, the length can be, for example, 10 μm or more and 300 μm or less, and the diameter can be, for example, 1 μm or more and 30 μm or less. The length and diameter can be actual measured values in a cross-sectional microscope photograph of the first member 12a.
[0020] The content of the rod-shaped particles 23 is not particularly limited as long as it does not significantly impair the effects of the present disclosure, but can be, for example, 5% by mass or more and 20% by mass or less with respect to the first material.
[0021] However, when the rod-shaped particles 23 contain carbon fibers, the carbon fiber content is preferably 5% by mass or more and 15% by mass or less with respect to the first material, which can improve the strength of the first member 12a against stress such as shear stress.
[0022] 3 is a cross-sectional view of the second member 12b. The second member 12b is made of a second material, which includes a second base resin 31 made of a fluororesin and a reinforcing agent 32 dispersed in the second base resin 31. The reinforcing agent 32 is preferably dispersed evenly throughout the second base resin 31, but may be unevenly distributed in some areas.
[0023] The second base resin 31 forms the outer shell of the second member 12b. The second base resin 31 is not particularly limited as long as it is a fluororesin, so long as it does not significantly impair the effects of the present disclosure, and for example, the above-mentioned examples of the constituent materials of the fluororesin particles 22 (FIG. 2) can be used. The second base resin 31 may be used alone or in any ratio and combination of two or more types.
[0024] The second base resin 31 preferably contains polytetrafluoroethylene, which can promote the formation of a transfer film 14 (FIG. 4) on the sliding surface 13 (FIG. 1) together with the fluororesin particles 22 (FIG. 2) in the first member 12a (FIG. 2).
[0025] The fluororesin particles 22 (FIG. 1) and the second base resin 31 are preferably made of the same type of fluororesin. In this way, the fluororesin particles 22 and the second base resin 31 can form a transfer film 14 of the same constituent material on the sliding surface 13, thereby facilitating transfer.
[0026] The reinforcing agent 32 improves the strength of the second member 12b (particularly the second base resin 31) against stress such as shear stress. The specific material of the reinforcing agent 32 is not particularly limited as long as it does not significantly impair the effects of the present disclosure. The reinforcing agent 32 may be used alone or in any combination of two or more kinds in any ratio.
[0027] The reinforcing agent 32 preferably contains at least one of copper, a copper alloy (an alloy mainly composed of copper, such as bronze), and carbon fiber. By using these materials, even if the reinforcing agent 32 falls off the second member 12b and gets into the sliding surface 13, the occurrence of scratches on the sliding surface 13 can be suppressed because the material is soft.
[0028] The form of the reinforcing agent 32 is not particularly limited as long as it does not significantly impair the effects of the present disclosure, but may be, for example, particulate. The particle size of the reinforcing agent 32 is also not particularly limited as long as it does not significantly impair the effects of the present disclosure, and may be any size.
[0029] The content of the reinforcing agent 32 is not particularly limited as long as it does not significantly impair the effects of the present disclosure, but can be, for example, 5% by mass or more and 30% by mass or less with respect to the second material.
[0030] The second material preferably further contains a solid lubricant 33. By containing the solid lubricant, a lubricating film (not shown) is formed on the sliding surface 13 (FIG. 1), thereby reducing friction between the second member 12b and the sliding surface 13 and further improving the wear resistance of the sliding member 12. The solid lubricant 33 may be used alone or in any combination of two or more kinds in any ratio.
[0031] The solid lubricant 33 preferably contains at least one of molybdenum disulfide and spherical carbon. By containing at least one of these, friction between the second member 12b and the sliding surface 13 can be reduced, wear resistance can be improved, and the strength of the second member 12b against stress such as shear stress can be improved. For example, in the case of molybdenum disulfide, the SS bond is weak, so that delamination occurs, and thus the solid lubricant exhibits solid lubricity.
[0032] The content of the solid lubricant 33 is not particularly limited as long as it does not significantly impair the effects of the present disclosure, but can be, for example, 1% by mass or more and 15% by mass or less with respect to the second material.
[0033] Returning to FIG. 1, the second member 12b is disposed adjacent to the first member 12a along the sliding surface 13. The term "adjacent" here means that the first member 12a and the second member 12b do not need to be in contact with each other in the direction of the sliding surface 13 (sliding direction), and any member is allowed to be disposed between the first member 12a and the second member 12b as long as it does not significantly impair the effect of the present disclosure. In the illustrated example, the first member 12a and the second member 12b are in contact with each other in the direction of the sliding surface 13. The first member 12a and the second member 12b are disposed continuously in the circumferential direction of the sliding member 12 along the sliding surface 13.
[0034] The first member 12a and the second member 12b are arranged so that the second member 12b is sandwiched between at least two of the first members 12a. In this way, even if the second base resin 31 (FIG. 3) in the second member 12b thermally expands, the second member 12b is sandwiched between the first members 12a, so that the deformation of the entire sliding member 12 due to thermal expansion can be kept within the design tolerance. In addition, a transfer film 14 (FIG. 4) can be formed on the sliding surface 13, improving the wear resistance of the sliding member 12. In the illustrated example, two first members 12a are provided, and when three or more first members 12a are provided, the second member 12b may be disposed between any two of the first members 12a.
[0035] 4 is a diagram illustrating the transfer film 14 formed during sliding. When the sliding member 12 slides on the sliding surface 13, a transfer film 14 made of a fluororesin is formed on the sliding surface 13.
[0036] The thermal expansion coefficient of the fluororesin particles 22 (FIG. 2) and the fluororesin constituting the second matrix resin 31 (FIG. 3) is relatively large. For this reason, if the sliding member 12 were made up of only the first member 12a or only the second member 12b, there is a possibility that deformation, uneven wear, and the like may occur, particularly in a high-temperature friction environment. A specific example of a high-temperature friction environment is the vicinity of the compression / expansion chamber 44 (FIG. 5) in a fluid machine 100 (FIG. 5) such as a rocking piston type reciprocating gas compressor.
[0037] Therefore, the sliding member 12 is composed of a first member 12a including a first base resin 21 (FIG. 2) having fluororesin particles 22 dispersed therein, and a second member 12b including a second base resin 31 made of fluororesin. The first base resin 21 made of a resin other than fluororesin has a high friction coefficient depending on the constituent material, and the transfer film 14 formed on the sliding surface 13 may peel off due to the second base resin 31. Therefore, by dispersing the fluororesin particles 22 in the first base resin 21, the friction coefficient of the first member 12a on the sliding surface 13 can be reduced, peeling of the transfer film 14 can be suppressed, and wear resistance can be improved.
[0038] On the other hand, with only the first member 12a, the fluororesin capable of forming the transfer film 14 originates only from the fluororesin particles 22, so there is still room for improvement in the degree of formation of the transfer film 14. Therefore, by using the second member 12b including the second base resin 31 made of fluororesin in addition to the first member 12a, the formation of the transfer film 14 can be promoted, and the friction coefficient can be reduced and the wear resistance can be improved.
[0039] In addition, in the sliding member 12, the first member 12a and the second member 12b mutually assist in the formation of a transfer film 14 (FIG. 4) on the metal member 11, suppressing wear. Furthermore, the materials other than fluororesin contained in the first base resin 21 and the second base resin 31, respectively (rod-shaped particles 23 (FIG. 2), reinforcing agent 32 (FIG. 3), and solid lubricant 33 (FIG. 3)), improve toughness or slipperiness. This can improve the wear resistance of the first member 12a and the second member 12b.
[0040] In addition, the presence of the first material, the second material, the fluororesin particles 22 (FIG. 2), the rod-shaped particles 23, the reinforcing agent 32, and the solid lubricant 33 in the sliding member 12 can be confirmed, for example, as follows. That is, for example, the surface or crushed matter of the first member 12a or the second member 12b can be easily identified by performing surface observation and chemical analysis using an optical microscope, energy dispersive X-ray analysis (EDX), X-ray photoelectron spectroscopy, infrared spectroscopy, or the like.
[0041] 1, the metal member 11 can be made of transition metals such as iron, nickel, molybdenum, chromium, titanium, copper, etc., and light metals such as aluminum, silicon, magnesium, etc. Specifically, the metal member 11 can be made of aluminum-based materials such as aluminum and aluminum alloys, copper-based materials such as copper and copper alloys, titanium-based materials such as titanium and titanium alloys, and iron-based materials such as iron and iron-nickel alloys.
[0042] The metal member 11 is, for example, a metal material with an untreated surface, but the surface of the metal material may be subjected to a surface treatment. In this case, the sliding member 12 comes into contact with and slides on the surface-treated surface. That is, the surface of the metal member 11 may be formed by the metal elements constituting the metal member 11, or may be formed by a surface treatment applied on the metal member 11.
[0043] The surface treatment formed on the surface of the metal member 11 is, for example, a surface coating artificially applied to the metal material, a natural oxide film, etc. The natural oxide film is, for example, aluminum oxide when the metal member 11 is aluminum, and iron oxide when the metal member 11 is iron. The surface coating is formed, for example, by a chemical vapor deposition (CVD) method, a physical vapor deposition (PVD) method, plating treatment, carburizing treatment, etc., and is made of a material containing at least one of aluminum, chromium, iron, phosphorus, nickel, and zinc. Specific examples include anodizing, aluminum plating, chromium plating, iron plating, nickel plating, zinc plating, etc.
[0044] 5 is a schematic diagram of a fluid machine 100 including the sliding member 12 of the first embodiment. In the illustrated example, the fluid machine 100 is a rocking piston type reciprocating gas compressor. The fluid machine 100 exhibits particularly significant effects when there is no sufficient lubricating oil or the like on the inner wall surface 411 (an example of the sliding surface 13 (FIG. 1)) and the fluid machine 100 is used in an oil-less manner, or when there is no lubricating oil at all and the fluid machine 100 is used in an oil-free manner. However, lubricating oil, grease, or the like may be present on the inner wall surface 411.
[0045] The fluid machine 100 includes a cylinder 41 (an example of a metal member 11 (FIG. 1)) and a piston 40 that reciprocates (moves up and down in the illustrated example) inside the cylinder 41. The piston 40 includes a sliding member 12 that slides on an inner wall surface 411 of the cylinder 41, and the sliding member 12 is composed of a piston body 42 (an example of a first member 12a (FIG. 1)) and a piston ring 43 (an example of a second member 12b (FIG. 1)). The piston ring 43 is, for example, annular, and is fitted into an annular groove (not shown) formed on the outer circumferential side surface of the disk-shaped piston body 42.
[0046] The space above the piston 40 in the cylinder 41 is provided with a compression / expansion chamber 44, which is a working space for compressing or expanding gas. The upper end of the cylinder 41 is closed by a partition plate 45, which is provided with an intake port 45a and an exhaust port 45b. The intake port 45a and the exhaust port 45b are provided with an intake valve 45c and an exhaust valve 45d, which are connected to pipes (not shown), respectively.
[0047] The operating principle of gas compression will now be described. The piston 40 is integrally formed with the connecting rod 46. As the crankshaft 47 rotates, the piston 40 moves up and down, causing gas to be sucked into the compression / expansion chamber 44 from the intake port 45a, and the gas is compressed in the compression / expansion chamber 44. The compressed gas is discharged to the outside through the discharge port 45b and collected by piping (not shown).
[0048] The piston 40 is a separate part from a connecting rod 46 that supports the piston 40. As the piston 40 moves up and down, the piston 40, which is formed by the sliding member 12 in the illustrated example, slides in point contact with an inner wall surface 411 of the cylinder 41. The connecting rod 46 may be made of metal or resin.
[0049] A coating may be formed on the inner wall surface 411 of the cylinder 41 by surface treatment of the metal member 11. For example, the inner peripheral surface of the cylinder 41 may be left as it is with a natural oxide film formed thereon, or may be anodized. Also, the inner peripheral surface of the cylinder 41 does not necessarily need to be coated with a coating.
[0050] The sliding member 12 may be used in mechanical devices that require good sliding properties, such as analytical devices, vacuum devices, and space-related equipment, in addition to the fluid machine 100 shown in FIG.
[0051] 6 is a cross-sectional view showing a sliding member 121 of the second embodiment. The sliding member 121 is similar to the sliding member 12 (FIG. 1) except that the arrangement order of the first member 12a and the second member 12b is different.
[0052] In the sliding member 121, the first member 12a and the second member 12b are arranged such that the first member 12a is sandwiched between at least two second members 12b. By arranging in this manner, the transfer film 14 (FIG. 4) can be formed starting from the multiple second members 12b having a fluororesin base material, and the formation of the transfer film 14 (FIG. 4) can be promoted. EXAMPLES
[0053] <Example 1> The first member 12a (FIG. 2) was produced from a first material including PPS as the first base resin 21 (FIG. 2), PTFE as the fluororesin particles 22 (FIG. 2), and carbon fiber as the rod-shaped particles 23 (FIG. 2). The fluororesin particles 22 and the rod-shaped particles 23 were dispersed throughout the first base resin 21. The content of the fluororesin particles 22 was 15% by mass relative to the first material. The content of the rod-shaped particles 23 was 10% by mass relative to the first material. The length and diameter of the rod-shaped particles 23 were 100 μm and 8 μm, respectively, as the average length and diameter measured by the above method.
[0054] The second member 12b (FIG. 3) was made of a second material including PTFE as the second base resin 31 (FIG. 3), bronze as the reinforcing agent 32 (FIG. 3), and molybdenum disulfide and spherical carbon as the solid lubricant 33 (FIG. 3). The reinforcing agent 32 and the solid lubricant 33 were dispersed throughout the second base resin 31. The content of the reinforcing agent 32 was 10 mass% relative to the second material. The content of the molybdenum disulfide was 5 mass% relative to the second material. The content of the spherical carbon was 10 mass% relative to the second material. Therefore, in Example 1, the total amount of the solid lubricant 33 composed of molybdenum disulfide and spherical carbon was 15 mass% relative to the second material.
[0055] FIG. 7 is a diagram for explaining a test method of a friction test. The sliding member 12 of Example 1 was produced so that the produced first member 12a and second member 12b were arranged on the sliding surface 13. The sliding member 12 was produced so that the first member 12a surrounded the second member 12b. The height H1 of the first member 12a in the vertical direction of the paper was 10 mm, and the width W1 in the horizontal direction of the paper was 10 mm. The height H2 of the second member 12b in the vertical direction of the paper was 5 mm, and the width W2 in the horizontal direction of the paper was 4 mm. The lengths (not shown) of the first member 12a and the second member 12b in the front depth direction of the paper were both shorter than the vertical length of a test piece 15 described later. The area ratio of the first member 12a to the second member 12b on the sliding surface 13 was 6:4.
[0056] The sliding member 12 was brought into contact with a test piece 15 made of an aluminum alloy plate (having a length (a direction from the front of the paper, not shown) of 20 mm, a width W3 of 43 mm, and a thickness H3 of 3 mm) having an anodized surface as the sliding surface 13, and was reciprocated in the left-right direction of the paper. The friction test conditions were as follows: contact surface pressure between the sliding member 12 and the test piece 15 of 3 MPa, friction speed of 0.4 m / s, distance of one reciprocation of 20 mm, and surface temperature of the test piece 15 (temperature of the sliding surface 13) of 110°C. Then, the total amount of wear when sliding was performed for a predetermined time in the friction test, and the friction coefficient during sliding for the predetermined time were measured. The results of the friction test will be described later with reference to Figs. 8 to 10.
[0057] <Comparative Example 1> A sliding member of Comparative Example 1 was produced and subjected to a friction test in the same manner as in Example 1, except that the fluororesin particles 22 (FIG. 2) and the rod-shaped particles 23 (FIG. 2) were not included. The results of the friction test will be described later with reference to FIGS. 8 to 10.
[0058] <Comparative Example 2> A sliding member of Comparative Example 2 was produced in the same manner as in Example 1, except that the second member 12b was not provided, and a friction test was conducted. The results of the friction test will be described later with reference to Figs. 8 to 10. The sliding member of Comparative Example 2 corresponds to the technology described in Patent Document 1 above.
[0059] The following Table 1 shows the constituent materials of the sliding members of Example 1, Comparative Example 1, and Comparative Example 2. "◯" indicates that the material was used, and "-" indicates that the material was not used.
[0060] [Table 1]
[0061] FIG. 8 is an energy dispersive X-ray analysis image (EDX) of the test piece surface after the friction test. The EDX-Al image shows the presence of aluminum on the test piece surface, and the EDX-F image shows the presence of fluorine on the test piece surface. There are almost no white areas in the EDX-Al image of Example 1, indicating that there is no aluminum on the surface. On the other hand, there are white areas in the EDX-F image of Example 1, indicating that there is fluorine on the surface. Therefore, it is believed that a transfer film 14 (FIG. 4) containing fluorine was formed on the surface of the test piece, which is why almost no aluminum, which is the constituent material of the test piece, was detected.
[0062] On the other hand, the EDX-Al images of Comparative Example 1 and Comparative Example 2 show the presence of white areas, indicating the presence of aluminum on the surfaces of the test pieces, whereas the EDX-F images of Comparative Examples 1 and 2 show no white areas, indicating the absence of fluorine on the surfaces. Therefore, it is believed that almost no fluorine-containing transfer film 14 (FIG. 4) was formed on the surfaces of the test pieces, and most of the aluminum that constitutes the test pieces was exposed as it was.
[0063] These results are believed to be the result of including fluororesin in both the first member 12a and the second member 12b. That is, it is believed that the transfer film 14 could be formed by providing the first member 12a and the second member 12b as in the sliding member 12 according to the present disclosure. However, when the fluororesin particles 22 are not used, for example, as in Comparative Example 1, the transfer film 14 formed by the second member 12b is peeled off by the first member 12a as described above, and it is believed that the transfer film 14 is unlikely to remain. In addition, since the second base resin 31, which is a fluororesin, is not used as in Comparative Example 2, it is difficult to form the transfer film 14, and it can be seen that there is room for improvement in the degree of formation of the transfer film 14.
[0064] Fig. 9 shows the test results of the wear amount (bar graph) and friction coefficient (plot) obtained in the friction test. Fig. 9 shows the total wear amount when sliding was performed for a predetermined time in the friction test shown in Fig. 7, and the average value of the friction coefficient during sliding for the predetermined time. In order to make the results easier to understand, the wear amount is expressed as a relative value when Comparative Example 2 is set to 100.
[0065] The coefficient of friction of Example 1 was lower than those of Comparative Examples 1 and 2. This is believed to be due to the formation of the transfer film 14 (FIG. 4), as described with reference to FIG. 8. The reduced coefficient of friction made it easier for the sliding member 12 to slide, and the amount of wear was reduced. For this reason, the sliding member 12 of the present disclosure exhibits excellent wear resistance.
[0066] On the other hand, when Example 1 is compared with Comparative Examples 1 and 2, the wear amount and friction coefficient of Comparative Examples 1 and 2 are both higher than that of Example 1. This is believed to be because, in Comparative Example 1, which does not include fluororesin particles 22, even if a transfer film 14 is formed, it is peeled off by the first member 12a, resulting in a large wear amount and friction coefficient. Also, in Comparative Example 2, which does not include the second member 12b, it is difficult to form the transfer film 14 in the first place, resulting in a large wear amount and friction coefficient.
[0067] In addition, in Comparative Examples 1 and 2, if the friction coefficient is reduced, the slipperiness is improved. However, if, for example, a decrease in the strength of the material against shear stress, excessive thermal expansion, etc., occurs at the same time, the amount of wear increases as a result. Therefore, the wear coefficient is one element for reducing the amount of wear, and simply reducing the friction coefficient does not necessarily reduce the amount of wear. For this reason, although the friction coefficient was smaller in Comparative Example 2, it is considered that the amount of wear was greater in Comparative Example 2. Therefore, in Example 1, the friction coefficient was reduced to make it easier to slip, and further, for example, the decrease in strength and excessive thermal expansion of the first member 12a and the second member 12b (both in FIG. 7) were suppressed, so it is considered that the amount of wear was reduced.
[0068] Fig. 10 is a diagram showing the correlation between the amount of wear (circle plots) and coefficient of friction (diamond plots) obtained in the friction test, and the content of the fluororesin particles 22 (Fig. 2). The results shown in Fig. 10 were obtained by simulating the friction test of Fig. 7, and were performed under the same conditions as in Example 1, except that the content of the fluororesin particles 22 (PTFE) in the first material was changed. The amount of wear is expressed as a relative value when the value when the blending amount of the fluororesin particles 22 is 70 mass% is set to 100.
[0069] The wear amount was particularly low when the content was in the range of 15% by mass or more and 30% by mass or less. Therefore, particularly high wear resistance was shown when the content was in this range. On the other hand, when the content was less than 15% by mass or more than 30% by mass, the wear amount tended to increase.
[0070] The friction coefficient showed a nearly constant value when the content was 15 mass% or more. This means that if the content was 15 mass% or more, a transfer film 14 (FIG. 4) with good slipperiness was formed on the test piece. Therefore, from the results in FIG. 10, it was found that the content of the fluororesin particles 22 is preferably 15 mass% or more and 30 mass% or less with respect to the first material.
[0071] As described above, by applying the sliding member 12 according to the present disclosure to the piston 40, which is a sliding part of a swing piston system in, for example, a reciprocating gas compressor, it is possible to improve the wear resistance of the piston 40. This makes it possible to extend the life of the piston 40, and for example, the maintenance cycle of the reciprocating gas compressor. [Explanation of symbols]
[0072] 100 Fluid machinery 11 Metallic parts 12 Sliding member 12a First member 12b Second member 13 Sliding surface 14 Transfer membrane 15 Test Pieces 21 First base material resin 22 Fluorine resin particles 23 Rod-shaped particles 31 Second base material resin 32 Reinforcement 33 Solid Lubricants 40 Piston 41 Cylinder 411 Inner wall surface 42 Piston body 43 Piston ring 44 Compression and expansion chamber 45 Partition 45a Inlet 45b Discharge port 45c Intake valve 45d Discharge valve 46 Connecting rod 47 Crankshaft
Claims
1. A sliding member that contacts a sliding surface, The sliding member is A first member made of a first material including a first base resin made of a resin other than a fluororesin and fluororesin particles and rod-shaped particles dispersed in the first base resin; a second member that is arranged adjacent to the first member along the sliding direction of the sliding member on the sliding surface, and that is made of a second material containing a second base resin made of a fluororesin and a reinforcing agent dispersed in the second base resin; A sliding member characterized by:
2. The first base resin contains at least one of polyphenylene sulfide and polyether ether ketone.
2. The sliding member according to claim 1.
3. The fluororesin particles contain at least one of polytetrafluoroethylene and a tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer.
3. The sliding member according to claim 1 or 2.
4. The rod-shaped particles include at least one of carbon fibers and glass fibers.
3. The sliding member according to claim 1 or 2.
5. The second matrix resin includes polytetrafluoroethylene.
3. The sliding member according to claim 1 or 2.
6. The reinforcing material includes at least one of copper, a copper alloy, or a carbon fiber.
3. The sliding member according to claim 1 or 2.
7. The second material further comprises a solid lubricant.
3. The sliding member according to claim 1 or 2.
8. The solid lubricant contains at least one of molybdenum disulfide and spherical carbon.
8. The sliding member according to claim 7.
9. The first member and the second member are disposed so that the second member is sandwiched between at least two of the first members.
3. The sliding member according to claim 1 or 2.
10. The first member and the second member are disposed such that the first member is sandwiched between at least two of the second members.
3. The sliding member according to claim 1 or 2.
11. The fluororesin particles and the second base resin are made of the same type of fluororesin.
3. The sliding member according to claim 1 or 2.
12. The content of the fluororesin particles is 15% by mass or more and 30% by mass or less with respect to the first material.
3. The sliding member according to claim 1 or 2.
13. The rod-shaped particles include carbon fibers, The content of the carbon fiber is 5% by mass or more and 15% by mass or less with respect to the first material.
13. The sliding member according to claim 12.
14. A cylinder; a piston having a sliding member that slides on an inner wall surface of the cylinder; The sliding member is A first member made of a first material including a first base resin made of a resin other than a fluororesin and fluororesin particles and rod-shaped particles dispersed in the first base resin; a second member that is arranged adjacent to the first member along the sliding direction of the sliding member on the inner wall surface and is made of a second material including a second base resin made of a fluororesin and a reinforcing agent dispersed in the second base resin; A fluid machinery characterized by:
Citation Information
Patent Citations
Composite piston and its manufacture
JP1987215166A
Piston for cylinder
JP1991074681A
Sealing device
JP2002372155A
Sliding material and fluid compressing machine
JP2009085051A
Compressor Piston
US20090193966A1